2005
DOI: 10.1086/428765
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Galaxy Shape on Luminosity and Surface Brightness Profile

Abstract: For a sample of 96,951 galaxies from the Sloan Digital Sky Survey Data Release 3, we study the distribution of apparent axis ratios as a function of r-band absolute magnitude and surface brightness profile type. We use the parameter ''fracDeV'' to quantify the profile type (fracDeV ¼ 1 for a pure de Vaucouleurs profile; fracDeV ¼ 0 for a pure exponential profile). When the apparent axis ratio q am is estimated from the moments of the light distribution, the roundest galaxies are very bright (M r $ À23) de Vauc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
94
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 49 publications
17
94
0
Order By: Relevance
“…Our ellipticities, inner and mid , are broadly consistent with the results from previous works which showed that massive, luminous early-type galaxies, most of which are presumably core-Sérsic galaxies, tend to be rounder ( 0.25) than their less luminous counterparts, i.e., the Sérsic galaxies, 0.25 (e.g., Davies et al 1983;Jaffe et al 1994;Ferrarese et al 1994;Faber et al 1997;Ryden et al 2001;Alam & Ryden 2002;Vincent & Ryden 2005;Lauer et al 2005;Ferrarese et al 2006;Emsellem et al 2007Emsellem et al , 2011Holden et al 2009;Cappellari et al 2011). Overall, our core-Sérsic galaxies have inner and outer ellipticity distributions with median ellipticities of med = 0.13 ± 0.01, and med = 0.20 ± 0.01, respectively ( Figure 5).…”
Section: Inner and Outer Core-sérsic Galaxy Ellipticitiessupporting
confidence: 91%
See 1 more Smart Citation
“…Our ellipticities, inner and mid , are broadly consistent with the results from previous works which showed that massive, luminous early-type galaxies, most of which are presumably core-Sérsic galaxies, tend to be rounder ( 0.25) than their less luminous counterparts, i.e., the Sérsic galaxies, 0.25 (e.g., Davies et al 1983;Jaffe et al 1994;Ferrarese et al 1994;Faber et al 1997;Ryden et al 2001;Alam & Ryden 2002;Vincent & Ryden 2005;Lauer et al 2005;Ferrarese et al 2006;Emsellem et al 2007Emsellem et al , 2011Holden et al 2009;Cappellari et al 2011). Overall, our core-Sérsic galaxies have inner and outer ellipticity distributions with median ellipticities of med = 0.13 ± 0.01, and med = 0.20 ± 0.01, respectively ( Figure 5).…”
Section: Inner and Outer Core-sérsic Galaxy Ellipticitiessupporting
confidence: 91%
“…Hao et al (2006) also arrived at similar conclusions regarding the relation between the ellipticities of early-type galaxies and their local density. Likewise, Ryden et al (2001) studied the relation between galaxy shape and age while Vincent & Ryden (2005; see also Alam & Ryden 2002) examined the dependence of galaxy shapes on the luminosities. These studies concluded that brighter galaxies with old stellar populations, such as the core-Sérsic galaxies, are rounder than their fainter counterparts which have young stellar populations (see also, e.g., Lauer et al 2005;Ferrarese et al 2006).…”
Section: Core-sérsic Galaxy Formation Shape and Orientationmentioning
confidence: 99%
“…They found that the AARD of elliptical galaxies shows no dependence on colour, suggesting that dust extinction is not important for this sample. The full population of elliptical galaxies was well characterized by a Gaussian distribution in the equatorial ellipticity with mean Q = 0.89 and a lognormal distribution of the flattening with mean F = 0.43, which corresponds to slightly oblate ellipsoids in agreement with Vincent & Ryden (2005). In a recent paper, Rodríguez & Padilla (2013) have used the SDSS-DR8 (Aihara et al, 2011) and the morphological information from Galaxy Zoo (Lintott et al, 2011) finding that elliptical galaxies have a mean value of F = 0.58 (Figure 2, right panels).…”
Section: Photometric Approachmentioning
confidence: 75%
“…All these improvements allowed to study the dependence of the intrinsic shape with other galaxy properties such as the luminosity, colour, physical size, and environment. Using data from the SDSS-DR3 (Abazajian et al, 2005) Vincent & Ryden (2005 found that bright galaxies (M r ≤ −21.84) with a de Vaucouleurs profile have an AARD consistent with a triaxiality parameter in the range 0.4 < T < 0.8, where Kimm & Yi (2007) were able to reproduce the AARD by using a combination of oblate, prolate, and triaxial galaxy populations. Following the early work of Tremblay & Merritt (1996), they assumed each population having a Gaussian distribution of their intrinsic axis ratios.…”
Section: Photometric Approachmentioning
confidence: 99%
“…Even if simplified, these simulations make clear predictions about the structure of baryon-free dark matter halos and the dependence of halo properties on mass and formation redshift (Navarro et al 2004;Diemand et al 2004). With regard to shapes, observations of elliptical galaxies yield only the projected isophotes, and thus determination of the intrinsic shape distribution requires either statistical analyses based on large samples (e.g., Ryden 1992Ryden , 1996Tremblay & Merritt 1995, 1996Ryden et al 1993;Alam & Ryden 2002;Vincent & Ryden 2005;Plionis et al 2006) or mapping of potentials via detailed kinematical data for individual galaxies (e.g., Franx et al 1991;Statler et al 2004). Isophotal studies reveal that luminous and faint elliptical galaxies have significantly different shape distributions: the latter have c/a h i % 0:75, while the former are flatter, c/a h i % 0:65 (Tremblay & Merritt 1996).…”
Section: Introductionmentioning
confidence: 99%